2002
DOI: 10.1097/00055735-200212000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Cataracts associated with systemic disorders and syndromes

Abstract: This review article examines the ophthalmic literature published on cataracts and systemic disease during the past year. Epidemiologically, the association between alcohol consumption and lens opacification is reviewed. Cataracts continue to be strongly associated with systemic diseases such as diabetes mellitus. Clinical, basic science reports and the results of the Blue Mountains Eye Study group on the morphology of diabetes-related cataracts are presented. Patients with neurologic disorders such as Wilson d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…This response was observed as LEC death and lens oxidation. The obtained results are in line with previous studies, in which cataracts under diabetic conditions have been found to be strongly associated with agedependent circulatory disorders and also dependent on diastolic blood pressure, the duration of diabetes, elevated glycosylated hemoglobin levels and lower intraocular pressure (19,20).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This response was observed as LEC death and lens oxidation. The obtained results are in line with previous studies, in which cataracts under diabetic conditions have been found to be strongly associated with agedependent circulatory disorders and also dependent on diastolic blood pressure, the duration of diabetes, elevated glycosylated hemoglobin levels and lower intraocular pressure (19,20).…”
supporting
confidence: 92%
“…These lens fiber cells were suggested to contain less Nrf2-dependent antioxidant protection, and the changes result in crystallin aggregation and oxidation in the posterior and cortical regions. Moreover, earlier findings have reported that diabetic cataracts are intensely associated with diabetic exposure time (19,20), where longer exposure results in an increased density of the cortical lens fiber cell layer.…”
mentioning
confidence: 90%
“…Current treatment modalities are effective in preventing 98% of vision loss, if treatment is provided at the appropriate time.There is additional evidence that the risk of cataract increases with increasing diabetes duration and severity of hyperglycemia 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…There is published evidence that the risk of cataract increases with an increased duration of diabetes and severity of hyperglycemia [22]. There is also a strong positive association between diabetes with primary open angle glaucoma, the most common form of glaucoma or elevated intraocular pressure in the absence of optic neuropathy [23,24].…”
Section: Discussionmentioning
confidence: 99%